2014
DOI: 10.2147/ijn.s56661
|View full text |Cite
|
Sign up to set email alerts
|

Support for the initial attachment, growth and differentiation of MG-63 cells: a comparison between nano-size hydroxyapatite and micro-size hydroxyapatite in composites

Abstract: Hydroxyapatite (HA) is considered to be a bioactive material that favorably influences the adhesion, growth, and osteogenic differentiation of osteoblasts. To optimize the cell response on the hydroxyapatite composite, it is desirable to assess the optimum concentration and also the optimum particle size. The aim of our study was to prepare composite materials made of polydimethylsiloxane, polyamide, and nano-sized (N) or micro-sized (M) HA, with an HA content of 0%, 2%, 5%, 10%, 15%, 20%, 25% (v/v) (referred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 39 publications
1
18
1
Order By: Relevance
“…Surfaces with nanostructures are found to preferably adsorb vitronectin—a glycoprotein involved in cell adhesion and spreading—due to its structural characteristics and chemical affinity (Lord, Foss, & Besenbacher, ). Supporting the enhanced adhesion process, cells adhered to surfaces loaded with nanostructured HA further expressed higher levels of beta‐actin and talin—proteins associated with focal adhesions and cytoskeletal activation, whose increased expression leads to a higher degree of cytoplasmic spreading (Filova et al, ), as presently verified for seeded cellulose/nHA scaffolds.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Surfaces with nanostructures are found to preferably adsorb vitronectin—a glycoprotein involved in cell adhesion and spreading—due to its structural characteristics and chemical affinity (Lord, Foss, & Besenbacher, ). Supporting the enhanced adhesion process, cells adhered to surfaces loaded with nanostructured HA further expressed higher levels of beta‐actin and talin—proteins associated with focal adhesions and cytoskeletal activation, whose increased expression leads to a higher degree of cytoplasmic spreading (Filova et al, ), as presently verified for seeded cellulose/nHA scaffolds.…”
Section: Discussionmentioning
confidence: 69%
“…Regarding the latter, previous works have shown that, comparatively to μHA, nHA particles greatly enhance osteogenesis through the upregulation of distinct signalling pathways able to induce osteogenic commitment (Huang et al, ; Liu et al, ). This was further verified within cultures grown on composite structures loaded with either μHA or nHA particles (Filova et al, ; Li et al, ), with the latter exerting an osteogenic stimulation similar to the one attained with the addition of osteogenic growth factors to the culture environment (Polini, Pisignano, Parodi, Quarto, & Scaglione, ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…55 The "grass-like" fibres could, to certain extent, promote the cell adherence. 56 Recent studies also confirmed that the hierarchical micro/nanoscale structure could activate the local immune response quickly, stimulate the cell transmembrane protein adhering and early adhesion of cells, 57,58 and promote deposition of HA and proliferation of osteoblasts. 59…”
Section: Cell Differentiationmentioning
confidence: 93%
“…Because the biochemical and nanofeature cues obviously exhibited temporal-dependent dominance on cell behaviors, the combined effect of RGD peptide and HA nanoparticles within OPF hydrogel systems elicited a better biological response than that of the individual components. Filova et al (2014) prepared composite materials made of polydimethylsiloxane, polyamide, and nano-sized (100 ± 50 nm) or micro-sized (100 ± 50 lm) HA, with an HA content of 0%, 2%, 5%, 10%, 15%, 20%, and 25% (v/v) (referred to as N0-N25 or M0-M25). Nano-sized HA supported cell growth, especially during the first 3 d of culture.…”
Section: Composite Scaffolds Fabricated By Synthetic Polymersmentioning
confidence: 99%